2010
DOI: 10.1152/ajpcell.00535.2009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy causes loss of dermal lymphatic vessels and interferes with lymphatic function by TGF-β1-mediated tissue fibrosis

Abstract: A, Cordeiro AP, Mehrara BJ. Radiation therapy causes loss of dermal lymphatic vessels and interferes with lymphatic function by TGF-␤1-mediated tissue fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 75 publications
7
124
2
Order By: Relevance
“…28 This effect, for example, would not diminish the action of chemotherapy in this region, since systemic treatment tends to be offered to the patients prior to radiotherapy. 29 On the assumption that the IMC incidental irradiation has a therapeutic impact, an interesting note is that precisely the group that received the higher doses to the IMC comprises mastectomy patients, regardless of whether an immediate reconstruction was performed or not.…”
Section: Discussionmentioning
confidence: 99%
“…28 This effect, for example, would not diminish the action of chemotherapy in this region, since systemic treatment tends to be offered to the patients prior to radiotherapy. 29 On the assumption that the IMC incidental irradiation has a therapeutic impact, an interesting note is that precisely the group that received the higher doses to the IMC comprises mastectomy patients, regardless of whether an immediate reconstruction was performed or not.…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of dermal lymphatic function caused by radiotherapy is described (Avraham et al, 2010), we showed that regeneration of avascular autotransplanted lymph node fragments is possible in previously irradiated regions. We exposed the rats to a single dose of radiation higher than that commonly used in human radiotherapy, so lymph node fragment regeneration in patients ought to be possible.…”
Section: Discussionmentioning
confidence: 64%
“…In future studies, we will apply the very recently described technique to visualize lymphatics in the rat (Suami et al, 2011). Assuming that superficial drainage in our rat model was totally destroyed by previous surgery and radiation, presence of local drainage seems a promising tool for future therapy, because radiation leads to a loss of dermal lymphatic vessels (Avraham et al, 2010). Regeneration of lymphatic vessels in irradiated regions seems to need longer than in nontreated areas.…”
Section: Regeneration Of Lymph Node Fragments In Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Our group has previously shown that fibrosis is a critical regulator of lymphatic function and lymphatic regeneration [14,15,23,24] and fibrosis is a clinical histopathologic hallmark of lymphedema. [25] Therefore, in these experiments we sought to determine if CD4 or CD8 cell inflammation contributes to fibrosis and lymphatic dysfunction in the mouse tail model of lymphedema.…”
Section: Cd4 + Cell Depletion Inhibits Fibrosis and Improves Lymphatimentioning
confidence: 99%